Effects of Co-administration of Extracts of Carica papaya Linn (Fam: Caricaceae) on Activity of Two Oral Hypoglycaemic Agents (2007)
Purpose: To investigate the interacting effects of co-administration of Carica papaya leaf extract on the hypoglycemic activity of metformin and glimepiride in an animal model. Method: Experimental factorial design was used to evaluate the individual and interaction influence of three variables ie nature (N), dose administered (C) and duration of administration (D), in a 23(=8) employed at two levels - ‘’high’’ and ‘‘low’’ - on blood glucose of diabetic rats on administration of ethanolic leaf extract of Carica papaya and two hypoglycemic agents, metformin and glimepiride. Unpaired t-test was used to test for significant difference due to administration of the combination Results: Extract of Carica papaya at 5.0 mg/kg produced significant blood glucose reduction with no significant reduction at the higher dose of 10 mg/kg (p>0.05). Changing nature from “low” (Carica papaya extract) to “high” (glimepiride or metformin) did not significantly change hypoglycemic activity. Generally, the ranking of the interacting effects was ND>CD>>NC for glimepiride/extract, and CD>ND>NC for metformin/extract. Administration of higher dose of the extract led to significant (p<0.01) increase in onset of activity of glimepiride. The onset of activity of metformin was not affected, but a significant lowering (p<0.05) of blood glucose was observed at 24 hr with all combinations of extract and metformin. Conclusion: Leaf extract of Carica papaya significantly delays the onset of hypoglycaemic activity of glimepiride, and increases the hypoglycaemic effect of metformin with the variablesinteracting differently for each drug-extract combinations.